Repeat urine cultures in children with urinary tract infection - Risky Vitria Prasetyo; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer (Paediatrica Indonesiana, 2012)
Background Urinary tract infections (UTIs) are the secondleading cause of infection in children, following respiratorytract infections. Repeat urine cultures after antibiotic treatmentare routinely obtained in clinical practice to verify proof ofbacteriologic cure. The American Academy of Pediatrics doesnot recommended repeat cultures, due to increased cost anddiscomfort to patients.Objective To determine the frequency of positive repeat urinecultures after 3 days of antibiotics in children 'With UTIs.Methods We conducted a retrospective study on childrenwith UTIs who visited the Division of Pediatric Nephrology,Department of Child Health at Dr. Soetomo Hospital, Surabayafrom January 2006 to December 2011. Results of repeat urinecultures were obtained after 3 days of antibiotic treatment.Descriptive statistics were used to analyze the data.Results Of the 779 pediatric UTI cases, repeat urine cultureswere performed in 264 (33.9%) cases. Of the 264 patients whocomprised our study, there were similar numbers of girls and boys(50.4% vs. 49.6%, respectively). The mean age of patients was43.9 (SD 1.59) months and 35.5% of subjects were aged under 1year. In the initial urine cultures of our subjects, Escherichia coliwas the most common organism found, v,ith 92 cases (34.8%),compared to 58 cases (21.9%) of Klebsiella pneumoniae and 29cases (10.9%) of Pseudom.onas aeruginosa. Repeat urine culturesshowed no bacterial growth in 168 cases (63.6%).Conclusion Mostly negative repeat urine cultures v,ill probablyobviate the need of this test in daily routine practice. [PaediatrIndanes.2012,52:170Â·4].